Asymmetric effects of climate change adaptation on energy transition in top clean and dirty energy-consuming countries - Mohamed Sami Ben Ali (14152038) (2026)
Climate change adaptation is increasingly recognized as a potential catalyst for macroeconomic shifts, yet its heterogeneous impact on energy systems remains underexplored. This study investigates the asymmetric effects of climate change adaptation on energy transition, systematically comparing the structural dynamics between the world's top clean and fossil-fuel-dependent (dirty) energy-consuming economies. To capture non-linearities and distributional threshold effects, we employ Multivariate Quantile Regression as the primary analytical framework, alongside Quantile-on-Quantile Granger Causality to map intensity-varying directional flows. Instrumental Variable Quantile Regression is utilized to ensure robustness against endogeneity. The empirical findings reveal a distinct structural divergence between the two economic profiles. In clean-energy‑leading economies, adaptation capacity exhibits a concave relationship with energy transition, characterized by early-stage acceleration followed by diminishing returns as institutional maturity is reached. Conversely, fossil-fuel-dependent economies demonstrate steep threshold responses; profound structural lock-in suppresses transition efforts at lower quantiles, requiring a critical, high-level mass of adaptive capacity to trigger meaningful systemic change. These findings provide novel empirical evidence that adaptation acts not merely as a defensive mechanism, but as a strategic driver of the energy transition subject to institutional path dependence. The study concludes that uniform climate policies are suboptimal. Policymakers in fossil-fuel-heavy economies must prioritize overcoming initial structural barriers through concentrated, front-loaded adaptation investments, whereas clean economies should shift focus toward optimizing institutional efficiency and grid resilience to sustain transition momentum. Other Information Published in: Science of The Total Environment License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.scitotenv.2026.181796